Detail Desain Sistem Penyediaan Air Bersih Menggunakan Sumber Mata Air (Studi Kasus DAS Citarik, Kecamatan Cimanggung, Kabupaten Sumedang - Nugeraha, Winardi Dwi; Oktiawan, Wiharyanto (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2008)
Water is one of the fundamental nedds of human being, but not everyone could easly access it. At kecamatan Cimanggung, Kabupaten Sumedang there are a few spring water that could be used, but there is no sufficient clean water supply system available. this has caused the people at the area found difficulties to obtain clean water.